VIBRIO PARALAEMOLYTICUS AND THE SEAFOOD INDUSTRY - NATARAJAN, R; ABRAHAM, MARTIN; NAIR, G BALAKRISH (Fishery Technology, 2017)
The role of Vibrio parahaemolyticus in food borne gastroenteritis outbreaks associated primarily with the consumption of contaminated seafoods has been well documented. Information pertaining to various aspects of its occurrence in seafoods, procedures for isolation and identification, generation time and inactivation profiles is discussed. Emphasis has been given to the response of V. parahaemolyticus to low temperatures, heating and antibacterial agents. The public health hazard posed by the pathogen is outlined and the guidelines for control are reviewed in detail.